A novel GSK-3 inhibitor binds to GSK-3β via a reversible, time and Cys-199-dependent mechanism. (15th June 2021) - Ghazanfari, Davoud; Noori, Mahboubeh S.; Bergmeier, Stephen C.; Hines, Jennifer V.; McCall, Kelly D.; Goetz, Douglas J.
Graphical abstract: Abstract: Glycogen synthase kinase-3 (GSK-3) has been implicated in numerous pathologies making GSK-3 an attractive therapeutic target. Our group has identified a compound termed COB-187 that is a potent and selective inhibitor of GSK-3. In this study, we probed the mechanism by which COB-187 inhibits GSK-3β. Progress curves, generated via real-time monitoring of kinase activity, indicated that COB-187 inhibition of GSK-3β is time-dependent and subsequent jump dilution assays revealed that COB-187 binding to GSK-3β is reversible. Further, a plot of the kinetic constant (kobs ) versus COB-187 concentration suggested that, within the range of concentrations studied, COB-187 binds to GSK-3β via an induced-fit mechanism. There is a critical cysteine residue at the entry to the active site of GSK-3β (Cys-199). We generated a mutant version of GSK-3β wherein Cys-199 was substituted with an alanine. This mutation caused a dramatic decrease in the activity of COB-187; specifically, an IC50 in the nM range for wild type versus >100 µM for the mutant. A screen of COB-187 against 34 kinases that contain a conserved cysteine in their active site revealed that COB-187 is highly selective for GSK-3 indicating that COB-187′s inhibition of GSK-3β via Cys-199 is specific. Combined, these findings suggest that COB-187 inhibits GSK-3β via a specific, reversible, time and Cys-199-dependent mechanism.